Bank Sampah Rawajati: Strenghthening Operational and Communication Strategy - Afriza, Eka Sri Dana; Jari , Maria Marice; Wicaksono , Hadid; Akil , Tasya Putri Sandi (Sekolah Tinggi Manajemen IPMI, 2025)
This Community Involvement Project (CIP) was conducted to support Bank Sampah Rawajati, which is a waste management organization based in South Jakarta. Three key issues were addressed by the project: inactive digital presence, insufficient operations, and underutilization of educational facilities, specifically in the TOGA (Taman Obat Keluarga) greenhouse. To overcome these issues, key programs were implemented, which are Digital Marketing & Communication Strengthening and Operational Optimization & Management. The first program involved reactivating the bank's Instagram account, designing consistent visual content templates, developing a one-month content calendar, and preparing the #TrashForGood campaign to increase public engagement. The second program introduced a digital bookkeeping system via Google Sheets, printed customer savings books, and created educational media, including TOGA identification cards and pocketbooks. Although the development of standard operating procedures (SOPs) was not completed due to time limitations, the program successfully delivered practical tools and fostered sustainable community engagement. This effort not only raised the profile and operational efficiency of Bank Sampah Rawajati but also provided valuable experience for social innovation and stakeholder engagement among students as well. Our outcomes highlight the potential of educational methodologies and digital technologies to make valuable contributions to environmental sustainability and community empowerment.